The politics of climate change in a neo-developmental state: The case of South Korea. Issue 1 (January 2021) - Kalinowski, Thomas
South Korea is the seventh largest emitter of CO2 and its climate-change mitigation policies are clearly insufficient. At the same time, the country has been very ambitious in implementing industrial policies promoting green technologies and international initiatives to support greenhouse gas mitigation in developing countries. What explains this discrepancy between weak emission goals and strong investments in green technology as well as ambitions to become a green 'global leader'? This article argues that the specific character of Korean climate policies can be understood in the context of Korea's legacy as a developmental state characterized by strong corporatist links between state and business as well as a weak civil society.